Factors influencing the intention of youth to adopt electronic voting in South Africa - Moletsane, Tankiso (Department of Information Systems, 2022)
Background: The rapid increase in the adoption of the internet in developing countries and the growth of citizen-centric e-government technologies has sparked interest in electronic voting (e-voting) systems. E-voting systems enable voters to participate in elections remotely, using internet-based technologies. In 2020, the Independent Electoral Commission of South Africa stated its intention to introduce e-voting to lower the costs of voting, improve electoral transparency and efficiency, and to improve overall voter participation. There is, however, little research to explain the factors that could potentially influence voters, particularly young people (18-35 years) who are a growing voting demographic with a declining interest in electoral participation. Objective: The primary objective of this research is to investigate the factors that influence the intention of young people to adopt electronic voting in South Africa. Secondarily, the study seeks to investigate how South African youth perceive e-voting. Research methodology: Using a deductive approach, a conceptual model with constructs from the technology acceptance model (TAM), the theory of planned behaviour (TPB), and the diffusion of innovation theory (DOI) is proposed. An online survey is used to collect data (n = 412) from South African youth between the ages of 18 – 35 years. Key Findings: Structural equation modelling and factor analysis applied on a pretested and pre-validated quantitative survey reveal that technology stickiness, access to ICT, skills in ICT, attitude towards ICT, relative advantage and political affiliation positively impact the intention to use e-voting. Eighty-one (81%) percent of respondents agree that they will use e-voting should it become available. Value of the study: The study contributions are twofold. First, the research proposes an empirically tested theoretical framework to assess the intentions of youths to participate in e-voting and second, the study the study makes recommendations for policymakers regarding the e-voting perceptions of young people.